The Relationship between Workload and Nurse Burnout at RSD Merah Putih Magelang - Pratama, Azesa Afiyata Elan; Widyanto, Puguh; Masithoh, Robiul Fitri (Prosiding University Research Colloquium, 2022)
Nurses are always tasked with caring for patients every day to improve the quality of health services. The different characteristics and needs of each patient, shift work system, responsibilities and high service demands can be a stressor for nurses. There are various factors that can affect the problem, namely workload and burnout on nurses. Burnout is a symptom of physical, emotional and mental exhaustion with feelings of low self-esteem due to prolonged stress. The impact of burnout experienced by nurses on others is felt by recipients of health services, namely patients. Workload is the amount of work that must be carried out by a position/organizational unit and is the product of the work volume and the time norm. The workload will have an impact on the quality of service in the hospital, namely on patient satisfaction and the healing process. Objective: To find out the relationship between workload and burnout at RSD Merah Putih Magelang. Methods: This type of research was descriptive correlation with cross sectional approach which data collection used purposive sampling technique with a sample of 66 respondents and the data was processed using the Spearman test. Results: The results of the Spearman rank test showed that there was a significant relationship between workload and nurse burnout with a value (p = 0.000 and r = 0.497). Conclusion: There is a relationship between workload and nurse burnout with moderate correlation strength.